INTROVERT VS EXTROVERT: AN ANALYSIS OF THE STUDENTS' PERSONALITY IN LEARNING SPEAKING IN SMAN 18 MAKASSAR - Nurhaliza Nurhaliza; Andi Hamzah Fansury; Rampeng Rampeng (Teaching English as a Foreign Language Overseas Journal, 2023)
The objective of the research is to know Introvert and Extrovert students in learning speaking in SMAN 18 Makassar. This research used qualitative method with phenomenology design. This research conducted in two steps such as questionnaire and interview test. The sample of this research is XII IPA-4 there are 13 students as respondents. The data collecting by using questionnaire and interview test. After conducted the research, the writer concludes that there is no effect of students’ personality in learning speaking. It was proved by the result of the questionnaire and interview test which there are eight students that has introvert personality and five students that has extrovert personality, and according to the interview test that given, most of the students has the same way in learning speaking which is watching movie, reading book, and listening to the songs. Therefore, according to the result of the research, the personality of introvert and extrovert students in SMAN 18 Makassar is not affected on their way in learning speaking. In addition, after this research, students can identified their personalities based on the questionnaires that given